2007
DOI: 10.1186/1471-2334-7-65
|View full text |Cite
|
Sign up to set email alerts
|

Oral infection of mice with Salmonella entericaserovar Typhimurium causes meningitis and infection of the brain

Abstract: Background: Salmonella meningitis is a rare and serious infection of the central nervous system following acute Salmonella enterica sepsis. For this pathogen, no appropriate model has been reported in which to examine infection kinetics and natural dissemination to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
5
31
1
Order By: Relevance
“…Significant progress has been made in understanding the molecular interactions between the BBB and microbial pathogens with the availability of in vitro tissue culture models of human BMEC (hBMEC) (Stins et al 1994;Weksler et al 2005) and in vivo animal models (Smith et al 1973;Doran et al 2002;Wickham et al 2007;Uchiyama et al 2009;Sheen et al 2010). Microbial interactions with the BBB may involve crossing of BMEC in a vacuole (transcytosis), through the intercellular junctional spaces ( paracytosis), or while inside a host cell (e.g., infected phagocyte) using it as a vehicle to cross the barrier (Trojan horse) (Kim 2008(Kim , 2010 (Fig.…”
Section: Pathogen Invasion Of the Bbbmentioning
confidence: 99%
“…Significant progress has been made in understanding the molecular interactions between the BBB and microbial pathogens with the availability of in vitro tissue culture models of human BMEC (hBMEC) (Stins et al 1994;Weksler et al 2005) and in vivo animal models (Smith et al 1973;Doran et al 2002;Wickham et al 2007;Uchiyama et al 2009;Sheen et al 2010). Microbial interactions with the BBB may involve crossing of BMEC in a vacuole (transcytosis), through the intercellular junctional spaces ( paracytosis), or while inside a host cell (e.g., infected phagocyte) using it as a vehicle to cross the barrier (Trojan horse) (Kim 2008(Kim , 2010 (Fig.…”
Section: Pathogen Invasion Of the Bbbmentioning
confidence: 99%
“…Human infection with Salmonella Typhi can be modeled in the laboratory through the infection of susceptible mice with Salmonella Typhimurium (34). In this model, systemic infection ensues and Salmonella can infect multiple organs, such as the gastrointestinal tract, brain, liver, spleen, and gallbladder (19,42). Many aspects of host colonization in this murine model are reminiscent of human Salmonella Typhi infection.…”
mentioning
confidence: 99%
“…Recently, Wickham et al (30) reported that oral infection of mice with wild-type S. enterica serovar Typhimurium strains can cause meningoencephalitis. We have confirmed these observations and determined that such infections also arise after inoculation with wild-type strains by the i.n.…”
mentioning
confidence: 99%